A Perspectiva de elos dos fluxos reversos de produtos e embalagens retornados no segmento de massas e biscoitos em uma indústria nacional de alimentos - Santos, Rodiney Marcelo Braga dos (2011)
This dissertation is to examine the configuration of the reverse logistics segment of pasta and biscuits in a food industry. The practice of reverse logistics is extremely necessary to consider the growth of reverse operations in recent years, so the companies and society as a whole seek to meet demands that arise from the need for economic development, social and environmental commitment, and legal guidelines; among others, are aspects that foster a reasonable attention to this issue. Still, the reverse logistics scenario implies a greater involvement and commitment of the entire supply chain processes in search of less aggressive and implementation of sustainable development. After noticing the relevance of analyzing the context in whom they are inserted as links in the reverse current in the food industry, specifically in the segment of pasta and biscuits, and the identification of needs analysis, we present the following research problem " how reverse logistics can contribute, while differential logistic processes in the food sector? "This study took a qualitative approach overall, having been chosen as a strategy based on case study in the food industry, focusing on a single national industry, Group M. Dias Branco S/A, which is consolidated in the Brazilian food company and its operations as the largest company in this sector. The decision to draw up a single case study supports the observations of Yin (2005), with rationale in the typical case, which in this case may represent a family company considered typical of many other family businesses, from which can be extracted information about the experience in the industry. The methodology included was considered the most feasible to allow the internal relations of understanding phenomena in their context, presented a case study and expression of the phenomena studied, required by the act of comparison. From the standpoint of nature, is classified as applied, its objectives, exploratory and descriptive, and methodological procedures regarding the research is classified into bibliographic, documentary and field, because data were collected in the company, through semi-structured interviews conducted with employees of the reverse logistics industry, in addition to in situ observations from the non-participant observation and questionnaire with three supermarket retailers (small and medium). The interpretation and analysis, primary and secondary, are identified in two sections, which are presented in the description field of research (one of the company and its processes and identifying other retail flows), reaching the configuration of the logistics reverse (object of study). Finally, a discussion contextualized the practice of reverse logistics company, in addition to the existing configuration of the links that comprise the reverse flow (aftermarket) segment of pasta and cookie company's focus.